2020
DOI: 10.1242/dev.188052
|View full text |Cite
|
Sign up to set email alerts
|

The FOXJ1 target Cfap206 is required for sperm motility, mucociliary clearance of the airways and brain development

Abstract: Cilia are complex cellular protrusions consisting of hundreds of proteins. Defects in ciliary structure and function, many of which have not been characterised molecularly, cause ciliopathies: a heterogeneous group of human syndromes. Here, we report on the FOXJ1 target gene Cfap206, orthologues of which so far have only been studied in Chlamydomonas and Tetrahymena. In mouse and Xenopus, Cfap206 was co-expressed with and dependent on Foxj1. CFAP206 protein localised to the basal body and to the axoneme of mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…Notably, 8 out of all the tested SNPs were predicted to change the binding motif site of transcription factors potentially involved in testicular function ( Figure 1 , Tables S5 and S8 ). For instance, rs3098174 and rs56398519 were predicted to change the TFBS of FOXJ1, a transcription factor specifically required for the formation of motile cilia and which has been reported as an important member of a pathway involved in sperm maturation in murine models [ 24 ]. Similarly, the rs3098171 SNP modified the TFBS of HSF1, a stress-inducible and DNA-binding transcription factor that plays a central role in the activation of the heat shock response (HSR), and which has been proposed essential for spermatogenesis [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, 8 out of all the tested SNPs were predicted to change the binding motif site of transcription factors potentially involved in testicular function ( Figure 1 , Tables S5 and S8 ). For instance, rs3098174 and rs56398519 were predicted to change the TFBS of FOXJ1, a transcription factor specifically required for the formation of motile cilia and which has been reported as an important member of a pathway involved in sperm maturation in murine models [ 24 ]. Similarly, the rs3098171 SNP modified the TFBS of HSF1, a stress-inducible and DNA-binding transcription factor that plays a central role in the activation of the heat shock response (HSR), and which has been proposed essential for spermatogenesis [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…They found that all the patients had hydrocephalus, arachnoid cysts, and choroid plexus hyperplasia, possibly related to CSF overproduction. Another cilia protein, Cfap206 is regulated by FOXJ1 and Cfap206 mutant mice develop hydrocephalus, Beckers et al [100]. Similarly, Zou et al [101] found that loss of another motile cilia protein, RSPH9, caused hydrocephalus and ependymal cell loss in mice, along with some parenchymal effects.…”
Section: Genetic Causes For Ventriculomegalymentioning
confidence: 99%
“…Immunofluorescence analysis has indicated that CFAP251 appears completely absent in the sperm cells of patients harboring CFAP206 mutations, indicating the important role of CFAP206 in CSC assembly or stability ( Shen et al, 2021 ). Beckers et al (2020) generated polyclonal antibodies to study CFAP206 localization and reported that it is located on the axoneme and basal bodies. Interruption of CFAP206 does not have a significant effect on sperm flagella morphology in mutant mice, but it significantly reduces the sperm motility by affecting the flagellar beat frequency.…”
Section: Pathogenic Genes and Their Function Inspermatogenesismentioning
confidence: 99%